(3GdJfGaS GdUjfj GdGeQjcj Hjf LOdjI GdUQGY h MJejI GdSjWQI (B:s 1991-2015 - (3GdOGdj, GdgGOj GdeHQhcs ((3GdLRGFQ(B: s (3cfhR GdMceI(B, s, 2016)
(3LGAJ gPg GdOQGSI HCQHY aUhd(B: (3ChdgG JMOK Yf GdYGde GdLOjO hGdSjGSI GdOhdjI HeG ajgG GdYdGbGJ GdSjGSjI GdOhdjI heGgh eWQhM Ydi GdfXGe GdYGdej GdLOjO, hHYOgG PcQ dfG GdYdGbGJ GdGbJUGOjI GdOhdjI eaGgjegG hGdYhGed GdeDKQI ajgG,Ke GfJbd Gdi GdUjf hcSH GdQgGf aj ZQH GaQjbjG GJLGg GdefGaSI GdCeQjcjI,hCgejI GdbGQI GdCaQjbjI aj GdSjGSI GdUjfjI hCSGdjH GdJYGhf eY Ohd GdbGQI GdEaQjbjI hYdGbJgG GdGbJUGOjI eYgG, HGdEVGaI Edi GdhLhO GdCeQjcj aj ZQH GaQjbjG Hjf GdeO hGdLRQ aj Xd GdefGaSI GdUjfjI, hCNjQG Jcde Yf LOdjI GdUQGY GdUjfj GdCeQjcj hCKQg Ydi Ohd ZQH GaQjbjG(B.s
(3eQGLY U(B.166s
Keywords: (3GdCMdGa GdYScQjIs; (3GdYdGbGJ GdNGQLjIs